Penerapan Pembelajaran STEAM untuk Mengembangkan Kreativitas Siswa Sekolah Dasar di Daerah Terluar Terdepan Tertinggal Indonesia - Eva Luthfi Fakhru Ahsani; Yva Alfiana Nurhaliza (Al Hikmah: Journal of Education, 2021)
The purpose of this research is to apply STEAM learning to develop the creativity level of Elementary School Students in the Outermost Disadvantaged Regions of Indonesia. The application of loose parts in STEAM learning is considered capable of developing the creativity of elementary school children. This type of research includes field research with qualitative descriptive methods. The subjects of this study were the fourth graders of SD Inpres Oeteta, Sulamu District, Kupang Regency, East Nusa Tenggara. Methods of data collection using interview techniques, observation, and documentation. The result of this research is that STEAM learning can develop students' skills in the fields of Science, Technology, Engineering, Art and Mathematical. using materials available in the environment. In addition, STEAM learning is able to make children have creativity in ways of thinking, solving problems and being able to think scientifically.